Logical Reconstruction and Practical Pathways of Financial Empowerment for Rural Revitalization through the “Five Major Initiatives” from the Perspective of Strategic Communication - Zhou, Yunzheng (Journal of Social Science and Humanities, 2026)
The 15th Five-Year Plan period represents a stage for comprehensively advancing rural revitalization and accelerating the modernization of agriculture and rural areas. Establishing a long-term mechanism for financial support in rural revitalization has become a core task in implementing the national strategy. The “Five Major Initiatives” of technology finance, green finance, inclusive finance, pension finance, and digital finance were proposed at the 2023 Central Financial Work Conference, providing a core framework for financial empowerment in rural revitalization during this period. This paper draws on the theory of strategic communication to systematically analyze the logical restructuring mechanism through which the “Five Major Initiatives” empower rural revitalization. However, at present, this process still faces challenges such as insufficient coordination among different components, absence of symbol adaptation, incomplete risk prevention and control system, and poor connection between the transmission chain and the service chain. To this end, it is necessary to promote the coordinated optimization of financial policy communication, media agenda-setting, institutional service innovation, and grassroots acceptance mechanisms at the strategic communication level. This will form a closed-loop system comprising four interlinked components: “policy guidance—communication empowerment—financial outreach—feedback and correction”. This approach will provide a framework for enhancing both the communication effectiveness and practical efficacy of relevant policies.